Role playing as contextual learning to improve mathematical communication skills of madrasah ibtidaiyah students - Wirdatul Hasanah; Sintha Sih Dewanti; Listriyah Listriyah (University of Muhammadiyah Malang, 2024)
Among the efforts to improve Mathematical Communication Skills (MCS) is to innovate learning models. This research aims to develop contextual role-playing learning products to improve Madrasah Ibtidaiyah (MI/ primary school) students’ MCS on valid and practical fraction material. The research and development (R&D) model of Define, Design, Development, and Dissemination (4D) was employed. The research subjects were second graders at MI Tahfidz El Muna Q, totaling 28 students. The instruments included validation guidelines, practicality guidelines, and MCS tests. Product effectiveness is tested using N-Gain. The results showed that the number of students completing the MCS after contextual role-playing learning was 89.28%, which is in the high category. The average N-Gain value obtained was 0.79, which is also in the high category. These findings show that contextual role-playing learning can potentially improve MI students’ MCS, especially in fraction material.